Conversion of traditional cropland into teak plantations strongly increased soil erosion in montane catchments of Southeastern Asia [Abstract only] - Evrard, O.; Ribolzi, Olivier; Huon, S.; Rouw, Anneke de; Silvera, N.; Latsachack, K.O.; Soulileuth, B.; Lefevre, I.; Lacombe, Guillaume; Sengtaheuanghoung, Oloth; Valentin, Christian (2017)
Soil erosion delivers an excessive quantity of sediment to rivers of Southeastern Asia. Land use is rapidly changing in this region of the world, and these modifications may further accelerate soil erosion in this area. Although the conversion of forests into cropland has often been investigated, much fewer studies have addressed the replacement of traditional slash-and-burn cultivation systems with commercial perennial monocultures such as teak plantations. The current research investigated the impact of this land use change on the hydrological response and the sediment yields from a representative catchment of Northern Laos (Houay Pano, 0.6 km²) where longterm monitoring (2002-2014) was conducted (http://msec.obs-mip.fr/). The results showed a significant growth in the overland flow contribution to stream flow (from 16 to 31%). Furthermore, sediment yields strongly increased from 98 to 609 Mg km-2. These changes illustrate the severity of soil erosion processes occurring under teak plantations characterized by the virtual absence of understorey vegetation to dissipate raindrop energy, which facilitates the formation of an impermeable surface crust. This counter-intuitive increase of soil erosion generated by afforestation reflects the difficulty to find sustainable production solutions for the local populations of Southeastern Asia. To reduce soil loss under teak plantations, the development of extensive agro-forestry practices could be promoted.